Class Struggle in Theory: the position of enunciation of philosophy and the Hegel/Spinoza debate - Hamza, Agon (2020)
The present work is an attempt to discuss the limits of Louis Althusser’s philosophical project. These limits are highlighted through a discussion of Hegel and Spinoza, which is in a sense the very thrust of Althusser’s work.